PENGGUNAAN ASSESSMENT AUTENTIK DALAM PEMBELAJARAN BERBASIS PROYEK UNTUK MENINGKATKAN KREATIVITAS SISWA TINGKAT ALIYAH - Masrizal (Program Studi Manajemen Pendidikan Islam, 2024)
Education in the modern era faces the challenge of developing 21st-century skills such as creativity and problem-solving, in addition to academic achievements. One approach widely used to achieve this goal is project-based learning with authentic assessment, which encourages students to think critically and creatively. This study aims to explore how the use of authentic assessment in project-based learning can enhance the creativity of senior high school students. The research method used was qualitative with a descriptive approach, involving observations and interviews with teachers and students. The results show that the application of project-based learning with authentic assessment can significantly improve students' creativity, especially in problem-solving and collaboration skills. The process-focused assessment provides more in-depth feedback for students' development. This study contributes to the development of relevant learning approaches for modern educational needs and assists teachers in designing more effective strategies to enhance students' creativity and skills.